THEORETICAL AND EXPERIMENTAL RESEARCH OF STRENGTH PROPERTIES OF SPINE BEAM OF FREIGHT CARS - Neduzha, L. O.; Shvets, A. O. (Science and Transport Progress, 2021)
Purpose. The purpose of this paper is to analyze the results of theoretical and experimental studies of the strength properties of rolling stock; search for design tools, modeling, selection, justification of the service life extension of freight cars and their elements. Methodology. The article is based on the finite element method (FEM). It makes possible to completely automate the calculation of mechanical systems, although, as a rule, it requires a much larger number of computational operations than the classical methods of mechanics. The modern level of development of computer technology opens wide opportunities for the introduction of FEM into engineering practice. FEM is implemented in many well-known and widely distributed software products that provide strength analysis of models of machines, mechanisms, structures, including the rolling stock of railways. Findings. The article presents an analysis of the theoretical and experimental studies of the strength properties of rolling stock elements on the example of the spine beam of freight cars; calculations were performed using a modern application program package. The presented example of use of the offered approach has shown its operation capacity and efficiency, as well as correctness of the research direction. The offered approach can be used when solving similar optimization tasks in research and developmental practice of transport mechanical engineering. Originality. The authors proposed me-thod of determining the reliability indicators and solving scientific and applied problem of calculating the elements of freight cars, taking into account the operation features and the loading mode impact. This allows determining their durability at the design stage. There were developed and investigated the models of the spine beam of a freight car, on the basis of which the dependences characterizing the stress-strain state of its elements were obtained. Scientifically substantiated results of the evaluation of strength properties of spine beams of freight cars were obtained depending on their design. The aspects related to the current state and development prospects of railway transport, the use of the software complex in the design and calculation of rolling stock in the railway industry are considered. Practical value. The theoretical and experimental studies of the strength properties of rolling stock elements were considered on the example of a spine beam in a freight car. Calculations were performed using a modern software package. The application of these results will contribute to increase the safety of freight cars and improve the technical and economic performance of railway transport.